Hurricanes - Allaby, Michael (New York : Facts On File, 1997)
Provides information about hurricanes, describing the conditions that lead to their formation, discussing what happens during the course of such storms, explaining how they are tracked and named, and looking at some historic hurricanes.
Includes index.
Books for the Teen Age (NYPL).
School Library Journal.
Wilson's Senior High School.
Young Adult
Keywords: Hurricanes; Hurricanes